Evaluation Behavior of Highland Vegetable Farmers on West Bandung Regency To Use Good Pesticide Practices - Rasiska, Siska; Sudarjat, Sudarjat; Dono, Danar; Suganda, Tarkus; Setiawan, Iwan (CROPSAVER, 2025)
Synthetic pesticides are one of the pest control substances most widely used by highland vegetable farmers, including insecticides and fungicides. This research aims to evaluate the use of pesticides by highland vegetable farmers in Lembang and Cisarua Districts, West Bandung Regency. The methods used in this research are surveys and observations. Interviews using questionnaires were conducted with 90 highland vegetable farmers, in-depth interviews with extension workers and exporter institutions. Secondary data was obtained from the horticultural crop agriculture service and the Agriculture, Fisheries, and Forestry Extension Center. These data were analyzed descriptively regarding the knowledge, awareness, and skills of highland vegetable farmers in using pesticides. The results of the research show that highland vegetable farmers in Lembang and Cisarua Districts, West Bandung Regency, know the information on labels, especially dosage, target pests, method of application, and type of plant, also know the function of pesticides, dangers, prohibitions on disposing of pesticide waste, and the reasons. Farmers know the SOP for pesticide use from promotional materials, and direct training, as well as from extension workers. Farmers buy and use their own pesticides at agricultural shops, considering the target organisms and efficacy based on information from fellow farmers. Farmers mix two types of pesticides with water as a solvent,  put it first in a bucket, and stir with a stirrer. Pesticides are applied at 10.00-15.00 until they are finished, then wash the hands. Pesticides are stored in a locked place, such as a warehouse, and out of reach of children, and the packaging is burned. Farmers need to be given counseling and training on the correct SOPs, starting from preparation to handling spray equipment and waste.